Chapter Métiers, effort and catches of a Mediterranean small-scale coastal fishery: the case of the gulf of Lion Marine Natural Parc - Morel, Maxence (Proceedings e report, 2020)
In the context of current fisheries crisis, this study aimed describing the characteristics of the artisanal fisheries in the Gulf of Lion Marine Natural Park located north-western Mediterranean. Catch Per Unit Effort and fishing effort were described on a spatio-temporal scale. Data were collected through questionnaires to fishers at landing sites for a one-year between 2019 and 2020. The most frequently used métiers were the hake gillnet and the sparids trammel net and gillnet, targeting two predominant species: hake (Merluccius merluccius) and gilthead seabream (Sparus aurata).